The impact of thunderstorm asthma on emergency department attendances across London during July 2013. Issue 8 (7th October 2013) - Elliot, A J; Hughes, H E; Hughes, T C; Locker, T E; Brown, R; Sarran, C; Clewlow, Y; Murray, V; Bone, A; Catchpole, M; McCloskey, B; Smith, G E
Abstract : Background: This study illustrates the potential of using emergency department attendance data, routinely accessed as part of a national syndromic surveillance system, to monitor the impact of thunderstorm asthma. Methods: The Emergency Department Syndromic Surveillance System (EDSSS) routinely monitors anonymised attendance data on a daily basis across a sentinel network of 35 emergency departments. Attendance data for asthma, wheeze and difficulty breathing are analysed on a daily basis. Results: A statistically significant spike in asthma attendances in two EDSSS emergency departments in London was detected on 23 July 2013, coinciding with a series of large violent thunderstorms across southern England. There was also an increase in the reported severity of these attendances. Conclusions: This preliminary report illustrates the potential of the EDSSS to monitor the impact of thunderstorms on emergency department asthma attendances. Further work will focus on how this system can be used to quantify the impact on emergency departments, thus potentially improving resource planning and also adding to the thunderstorm asthma evidence-base.